2013
DOI: 10.1073/pnas.1309729110
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of microscopic bacterial communities

Abstract: Bacteria communicate via short-range physical and chemical signals, interactions known to mediate quorum sensing, sporulation, and other adaptive phenotypes. Although most in vitro studies examine bacterial properties averaged over large populations, the levels of key molecular determinants of bacterial fitness and pathogenicity (e.g., oxygen, quorum-sensing signals) may vary over micrometer scales within small, dense cellular aggregates believed to play key roles in disease transmission. A detailed understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
237
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(239 citation statements)
references
References 41 publications
0
237
0
2
Order By: Relevance
“…In addition, Hoffman et al have demonstrated that the P. aeruginosa exoproduct 4-hydroxy-2-heptylquinoline-N-oxide (HQNO) could protect S. aureus from killing by the aminoglycoside tobramycin in S. aureus-P. aeruginosa cocultures by suppressing S. aureus respiration (24). This type of "bystander" protection was also seen in the production of ␤-lactamases by P. aeruginosa, which were thought to protect S. aureus from ampicillin treatment in 3-dimensionally (3D) printed S. aureus-P. aeruginosa bacterial communities (46). Accumulation of environmental DNA (eDNA) in cocultures represents another possibility that could be examined further.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Hoffman et al have demonstrated that the P. aeruginosa exoproduct 4-hydroxy-2-heptylquinoline-N-oxide (HQNO) could protect S. aureus from killing by the aminoglycoside tobramycin in S. aureus-P. aeruginosa cocultures by suppressing S. aureus respiration (24). This type of "bystander" protection was also seen in the production of ␤-lactamases by P. aeruginosa, which were thought to protect S. aureus from ampicillin treatment in 3-dimensionally (3D) printed S. aureus-P. aeruginosa bacterial communities (46). Accumulation of environmental DNA (eDNA) in cocultures represents another possibility that could be examined further.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatives have been proposed, such as integration of an electrochemical sensor for real-time analysis (56), yet they are not widespread and make fabrication and operation more complex. A second limitation is that most microfluidic devices used in microbial studies to date are essentially two-dimensional, with very few exceptions (57). To attain a closer representation of natural habitats, it will be important in the future to introduce a three-dimensional component, as was done in tissue engineering (58,59).…”
Section: A New Opportunity To Explore the Role Of A Dynamic Environmementioning
confidence: 99%
“…The protein-based walls and roof of the microtrap define aggregate size and shape in three dimensions and are permeable to many small molecules. Cells confined within microtraps divide at normal rates and reach maximum cell density (10 12 cells mL −1 ) while maintaining cell numbers typical of natural aggregates (14,28,42).Using microtraps, our group showed that as few as 2,600 P. aeruginosa cells engage in QS-mediated behaviors when present at maximum density (42). This work used a cell-based biosensor, in which production of GFP served as a proxy for QS-mediated communication (14,42).…”
mentioning
confidence: 99%